Yield Regulation in the Forests of West Bengal - Roy, M. P. (Indian Forester, 1961)
The Forests of West Bengal have been divided into four geographical zones, viz., the Himalayan hills, the Duars, the Sunderbans and the Laterite zone. The floristics of each zone have been described. Shorea robusta is the only species which occurs gregariously in the Tista Valley, the Rangeet Valley, the Duars and the Laterite zone. Elsewhere the crop consists of an irregular mixture of a large number of species. Natural regeneration is inadequate except for some riverain species. The system of clear-felling followed by artificial regeneration with the help of taungya is applied in the Himalayan hills and the Duars to all such forests as are fit for conversion into a normal forest. Selection system is adopted for the riverain w forests and the Sunderbans. In the Laterite zone the long practised system of coppice with standards is followed. In the clear-felling system the yield is regulated by area alone. Only cultivable areas are taken into consideration during calculation. In the hills an allowance of 10% is made for retention of protection belts at necessary places. The age of the oldest plantation is tested with the conversion. Period to atisfy the condition of exploitability of the oldest plantation at the end of conversion. In the riverain forests managed under the selection system, the yield of important species like khair, sissoo and semul is regulated by number of trees. Selection-felling of species in the riverain forests as well as the forests of the Sunderbans is regulated by area. In the coppice forests of the laterite zone, area forms the basis for yield regulation. Felling is so distributed over the felling series containing crops of various densities as to give roughly equal volume-yield each year.